The Effectiveness of Leaflet-Based Balanced Nutrition Education on Improving Students’ Knowledge at Elementary School 2 Toronipa, Southeast Sulawesi, Indonesia - Purnamasari, Anisa; Nofitasari, Ari; Apriawal, Jabbal; Andriani, Rina; Saranani, Selpirahmawati (PT. Nursing Genius Care, 2025)
Background: The nutritional status of elementary school-aged children is a crucial factor in determining the quality of future human resources. However, limited nutritional knowledge among children remains a challenge, particularly in coastal areas with restricted access to information. Purpose: This study aims to assess the effectiveness of leaflet-based educational media in improving students' knowledge about balanced nutrition at Elementary School 2 Toronipa, Konawe Regency, Southeast Sulawesi, Indonesia. Methods: This research employed a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 45 students from grades III, IV, and V, selected through total sampling. The research instrument was a multiple-choice questionnaire developed based on the Balanced Nutrition Guidelines from the Indonesian Ministry of Health. The study procedure included a pretest, an educational intervention using leaflets, and a posttest. Results: The results showed that before the intervention, the majority of students had moderate (51.1%) and low (31.1%) levels of knowledge. Following the intervention, there was a significant increase in the high knowledge category to 73.4%, while the low category decreased to 2.2%. The average knowledge score improved from 11.3 to 16.6. The paired sample t-test indicated a statistically significant difference (p = 0.000; p < 0.05), confirming the effectiveness of the leaflet in enhancing students’ nutritional knowledge. Conclusion: Leaflets are an efficient, easy-to-understand, and engaging educational medium for elementary school children. These findings have positive implications for school-based nutrition education programs, especially in regions with limited access to information. Leaflet media can be integrated into health promotion programs to improve nutritional literacy and support healthy lifestyles from an early age.